Optimalisasi Supervisi Akademik dalam Meningkatkan Mutu Pembelajaran di SMPIT Bengkulu Selatan - Muhammad Shidiq; Desy Eka Citra Dewi (Jurnal Ilmiah Edukatif, 2023)
Supervision plays a very important role in improving the quality of learning. Supervision or supervisors have a strategic role in providing services to teachers who have difficulties or a decrease in their competence. Therefore, academic supervision is one of the important programs that must be implemented by school principals in fostering teachers to improve learning quality. The purpose of this study was to determine the improvement of learning quality through academic supervision. The research method used is descriptive qualitative method. Data collection techniques used by observation, documentation, and principal interviews. Primary data sources were generated from observation, documentation and interviewing the principal at SMPIT Al-Qolam, and secondary data were generated from documents, journals and books. The results showed that: Academic Supervision in Junior High School (SMP) has been carried out planning, organizing, implementing, guided by predetermined planning, has carried out learning evaluation, so that it can be known to improve the quality of learning.